POETRY AND FICTION BY MYKOLA VINGRANOVSKYJ IN ENGLISH TRANSLATIONS - Підопригора, Світлана; Кисіль, Вікторія (Taras Shevchenko National University of Kyiv (Ukraine), 2022)
The article examines the poetry and fiction by Mykola Vingranovskyj in English translations. Attention is paid to the chronological sequence of translations, the figures of translators and the works selected for translation, their equivalence to the original. The first translation of M. Vingranovskyj's fiction (the short story "White Flowers") appeared with the assistance of Yu. Lutsky in Canada and aimed at popularizing Ukrainian literature among students. The short story opens the extremely lyrical world of Mykola Vingranovskyj, where the story revolves not around the event, but around the feelings, which brings the short story closer to poetry. The novella was included to the anthology (Modern Ukrainian Short Stories, 1973) as the example of the prose of the sixties (shistdesyatnyky), which departed from socialist-realist ideological canons and turned to the emotional and expressive potential of artistic language. The translation of Yuri and Moira Lutsky is marked by the desire to convey as fully as possible the author's individual style, including figurative metaphor, to create a text equivalent to the original in communicative orientation. The collection Summer Evening (1987), translated by Anatoliy Bilenko, was published after M. Vingranovskyj was awarded the Taras Shevchenko National Prize of Ukraine (1984). The collection includes stories for children's audiences, conveying children's perception of the world: Chest, Shaggi, The Gosling, Good Night, What Makes the World Spin, Summer Evening. A. Bilenko's translations are notable for the adequacy of the reproduction of artistic and stylistic features of the original, semantic equivalence. Some translated poems, which emphasize the civic component (Sistine Madonna, To My Sea, On the Golden Table, The First Lullaby, Star Prelude) were included to the anthology of Ukrainian poetry (Anthology of Soviet Ukrainian Poetry, 1982), and Russian translators were involved in translating the poems (Dorian Rottenberg, Michael McGreg), which significantly reduced the artistic value of poetry. During the times of independent Ukraine, competitions for translations to the writer's anniversaries were initiated. However, translated works have not been published in collections and anthologies. Active work on translations of M. Vingranovskyj's works is still ahead.

Розглядаються поетичні та прозові твори Миколи Вінграновського в англомовних перекладах. Звернено увагу на хронологічну послідовність появи перекладів, постаті перекладачів та на твори, які обиралися для перекладу, їхню еквівалентність оригіналу. Перший переклад прозового твору М. Вінграновського (новела "Білі квіти") з'явився за сприяння Ю. Луцького в Канаді й мав на меті популяризацію української літератури серед студентства. Новела відкриває надзвичайно ліричний світ Миколи Вінграновського, де оповідь обертається не навколо події, а навколо почуттів, що наближає новелу до поезії. Новела ввійшла до антології ("Modern Ukrainian Short Stories", 1973) як приклад прози шістдесятників, які відходили від соцреалістичних ідеологічних канонів і зверталися до емоційно-виражального потенціалу художньої мови. Переклад Юрія та Мойри Луцьких відзначається прагненням якомога повніше передати авторський індивідуальний стиль, зокрема образну метафоричність, створити текст, еквівалентний оригіналу за комунікативною спрямованістю. Збірка "Літній вечір" ("Summer evening", 1987) у перекладі Анатолія Біленка побачила світ після присудження М. Вінграновському Національної премії України імені Тараса Шевченка (1984). До збірки ввійшли твори, орієнтовані на дитячу аудиторію, що передають дитяче одивнене сприйняття світу: "Скриня" ("The chest"), "Волохань" ("Shaggi"), "Гусенятко" ("The gosling"), "На добраніч" ("Good Night"), "Низенько зав'язана" ("What Makes the World Spin"), "Літній вечір" ("Summer Evening"). Переклади А. Біленка відзначаються адекватністю відтворення художньо-стилістичних рис оригіналу, змістовою еквівалентністю. Окремі перекладені поезії, у яких усе ж більше акцентується громадянська складова ("Сікстинська мадонна" ("Sistine Madonna"), "Моєму морю" ("To My Sea"), "На золотому столі" ("On the Golden Table"), "Перша колискова" ("The First Lullaby"), "Зоряний прелюд" ("Star Prelude"), увійшли до антології української поезії ("Anthology of Soviet Ukrainian Poetry", 1982). До перекладу поезій були залучені російські перекладачі (Уолтер Мей, Доріан Роттенберг, Майкл МакГрег), що значно знизило художню вартість поезій. За часів незалежної України було зініційовано конкурси перекладів до ювілеїв письменника. Однак перекладені твори не були опубліковані в збірках та антологіях. Активна робота над перекладами творів М. Вінграновського ще попереду.
ПОЕТИЧНІ Й ПРОЗОВІ ТВОРИ МИКОЛИ ВІНГРАНОВСЬКОГО В АНГЛОМОВНИХ ПЕРЕКЛАДАХ
Keywords: literary translation; short story; individual style; figurative expressions; Ukrainianness; equivalence; художній переклад; новела; індивідуальних стиль; образні вислови; українськість; еквівалентність перекладу